Pengaruh Labelisasi Halal, Merek dan Harga Terhadap Keputusan Pembelian Minuman Chatime - Dendy Khresna Bayu; Gumoyo Mumpuni Ningsih; Livia Windiana (Hasanuddin University, 2020)
Many manufacturers who opened the business of the beverage industry in Malang, especially in business drink bubble tea, one of which is brand Chatime. The purpose of this study was to analyze the effect of the product, the labeling of halal, brand, and price on the decision of purchasing of drinks Chatime. The sampling technique using Purposive Sampling, with the number of respondents 120 and using multiple linear regression analysis. Research results dominate characteristics of respondents by the female gender with the age range of 18-28 years old, college education, and with an income range of Rp. 1000.001 - Rp. 2000.000. The results of the research to variable product values got the significance of 0.000, which means the influence on purchase decisions, the significance value of the variable labeling of halal namely 0,653 which means it does not affect the purchase decision, the value of significance variable brand that 0,521 which means it does not affect the purchase decision, and the value of the significance of the price variable that is to 0.033, which means the price variables affect the purchase decision of beverage Chatime. The company should maintain the quality of the product and the price, but it imprints the halal label on the packaging and always innovating on the product sold. Keyword : Purchase Decision, Product, Chatime